Oxyresveratrol inhibits IL-1β-induced inflammation via suppressing AKT and ERK1/2 activation in human microglia, HMC3 - Phateep Hankittichai (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Oxyresveratrol (OXY), a major phytochemical component derived from several plants, has been proved to have several pharmacological properties. However, the role of OXY in regulating neuroinflammation is still unclear. Here, we focused mainly on the anti-neuroinflammatory effects at the cellular level of OXY in the interleukin-1 beta (IL-1β)-stimulated HMC3 human microglial cell line. We demonstrated that OXY strongly decreased the release of IL-6 and MCP-1 from HMC3 cells stimulated with IL-1β. Nevertheless, IL-1β could not induce the secretion of TNF-α and CXCL10 in this specific cell line, and that OXY did not have any effects on reducing the basal level of these cytokines in the sample culture supernatants. The densitometry analysis of immunoreactive bands from Western blot clearly indicated that IL-1β does not trigger the nuclear factor-kappa B (NF-κB) signaling. We discovered that OXY exerted its anti-inflammatory role in IL-1β-induced HMC3 cells by suppressing IL-1β-induced activation of the PI3K/AKT/p70S6K pathway. Explicitly, the presence of OXY for only 4 h could strongly inhibit AKT phosphorylation. In addition, OXY had moderate effects on inhibiting the activation of ERK1/2. Results from immunofluorescence study further confirmed that OXY inhibited the phosphorylation of AKT and ERK1/2 MAPK upon IL-1β stimulation in individual cells. These findings suggest that the possible anti-inflammatory mechanisms of OXY in IL-1β-induced HMC3 cells are mainly through its ability to suppress the PI3K/AKT/p70S6K and ERK1/2 MAPK signal transduction cascades. In conclusion, our study provided accumulated data that OXY is able to suppress IL-1β stimulation signaling in human microglial cells, and we believe that OXY could be a probable pharmacologic agent for altering microglial function in the treatment of neuroinflammation.